CRIME AND REVENGE IN UM CRIME MYSTERIOSO, BY MARY ELIZABETH BRADDON - Augusti, Valéria; Damião dos Santos, Tassiane Andreza (Revista de Letras, 2025)
This article is based on an investigation into the process of circulation and critical reception of the works of British novelist Mary Elizabeth Braddon (1835 – 1915) in the Province of Pará between the years 1880 and 1900, and then discusses the issue of the crime of revenge in the novel Um crime mysterioso translation of Henry Dunbar; the story of an outcast, published in 1864. With this in mind, it first provides a brief introduction to the author and the sensation novel genre. It then demonstrates how her novels circulated in nineteenth-century Belém, whether in the form of serial novels, in Portuguese translations published in the local press, or in bookstores and reading rooms located in the city. Finally, the article discusses the role of crime and revenge in the economy of the narrative, also paying attention to the use of disguise and peripeteia as important narrative strategies for maintaining suspense.